Haptics - Jones, Lynette (Gildan Audio, 2019)
An accessible, nontechnical overview of active touch sensing, from sensory receptors in the skin to tactile surfaces on flat screen displays. Haptics, or haptic sensing, refers to the ability to identify and perceive objects through touch. This is active touch, involving exploration of an object with the hand rather than the passive sensing of a vibration or force on the skin. The development of new technologies, including prosthetic hands and tactile surfaces for flat screen displays, depends on our knowledge of haptics. In this volume in the MIT Press Essential Knowledge series, Lynette Jones offers an accessible overview of haptics, or active touch sensing, and its applications. Jones explains that haptics involves integrating information from touch and kinesthesia-that is, information both from sensors in the skin and from sensors in muscles, tendons, and joints. The challenge for technology is to reproduce in a virtual world some of the sensations associated with physical interactions with the environment.